2019
DOI: 10.4314/ijbcs.v13i4.24
|View full text |Cite
|
Sign up to set email alerts
|

Prévalence et transmission du Virus de l’Immunodéficience Humaine de la mère à l’enfant à N’Djamena

Abstract: La femme enceinte infectée par le virus de l'immunodéficience humaine constitue un risque potentiel pour le nouveau-né. Au Tchad, les données sur la transmission verticale du virus ne sont pas disponibles. C'est pourquoi une étude transversale rétrospective et prospective a été effectuée à N'Djamena, dans le but de déterminer la prévalence du virus chez les femmes enceintes et la transmission maternelle. Des fiches ont été utilisées pour la collecte de données. Les anticorps anti VIH sont recherchés dans le sé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…This result is lower than that of Fatoumata [26] who found 17.65% at the Gabriel Touré University Hospital in Mali. In contrast, Hota and collaborators [27] found in their study an HIV/AIDS prevalence of 14.8% among children born to mothers living with HIV in N'Djamena, Chad (Figure 4).…”
Section: Resultsmentioning
confidence: 73%
“…This result is lower than that of Fatoumata [26] who found 17.65% at the Gabriel Touré University Hospital in Mali. In contrast, Hota and collaborators [27] found in their study an HIV/AIDS prevalence of 14.8% among children born to mothers living with HIV in N'Djamena, Chad (Figure 4).…”
Section: Resultsmentioning
confidence: 73%
“…The present prevalence is significantly lower compared to the 2016 and 2019 sentinel surveys with 5.75% and 4.26% respectively among pregnant women (12,13), including the results of studies which reported HIV prevalences of 5.70% (95% CI: 4.93-6.40), 6% (3.0-10.2%) and 7.8% respectively among pregnant women in Cameroon (1820). Furthermore, the respective prevalence rates of 9.2% and 7.22% reported in the countries of Chad and Nigeria are also of relevance (21,22). Our findings therefore reflect the declining trend of HIV among pregnant women in Cameroon (7.6% in 2009 to 2.9% in 2016 (19,23) and from 3.4% in 2018 to 2.1% in 2022 (24–26).…”
Section: Discussionmentioning
confidence: 99%